Measurement of emerging neurocognitive and language skills in the HEALthy Brain and Child Development (HBCD) study - Julie A. Kable; Alexandra S. Potter; Natacha Akshoomoff; Patricia M. Blasco; Stefanie C. Bodison; Lucia Ciciolla; Sherry DeGray; Zoe Hulce; Emily S. Kuschner; Britley Learnard; Monica Luciana; Alexandra Perez; et al. (Developmental Cognitive Neuroscience)
The HEALthy Brain and Child Development (HBCD) study, a multi-site prospective longitudinal cohort study, will examine human brain, cognitive, behavioral, social, and emotional development beginning prenatally and planned through early childhood. The study plans enrolling over 7000 families across 27 sites. This manuscript presents the measures from the Neurocognition and Language Workgroup. Constructs were selected for their importance in normative development, evidence for altered trajectories associated with environmental influences, and predictive validity for child outcomes. Evaluation of measures considered psychometric properties, brevity, and developmental and cultural appropriateness. Both performance measures and caregiver report were used wherever possible. A balance of norm-referenced global measures of development (e.g., Bayley Scales of Infant Development-4) and more specific laboratory measures (e.g., deferred imitation) are included in the HBCD study battery. Domains of assessment include sensory processing, visual-spatial reasoning, expressive and receptive language, executive function, memory, numeracy, adaptive behavior, and neuromotor. Strategies for staff training and quality control procedures, as well as anticipated measures to be added as the cohort ages, are reviewed. The HBCD study presents a unique opportunity to examine early brain and neurodevelopment in young children through a lens that accounts for prenatal exposures, health and socio-economic disparities.